Dilemma in diagnosing Metabolic Disorder: A case of Galactokinase Deficiency with an unusual presentation - Rajbhandari, Prasun; Rimal, Hem Sagar; Dahal, Sonia (Birat Journal of Health Sciences, 2021)
An infant with metabolic disorder can have vague presentations like repeated chest infections, feeding intolerance and failure to thrive. This may lead to a diagnostic dilemma. Detailed clinical history together with biochemical investigations are must to reach a diagnosis. Galactokinase Deficiency (GKD) has a varied presentation with some features like microcephaly, juvenile cataracts and failure to thrive. We encountered a case of GKD in an infant in which there was an absence of cataracts. Raised Immunoreactive Trypsinogen (IRT) in Newborn Screening was strongly suggestive of Cystic Fibrosis (CF), however Genetic Analysis revealed a heterozygous missense variation in EXON4 of the GALK1 GENE, confirming the diagnosis of GKD. Hence, this case highlights the importance of considering different metabolic disorders as differential diagnoses of one another even in absence of a typical feature of a particular disorder.